Navigating Freedom of Speech in Social Media: Reconstruction of the Crime of Defamation in the Era of the New Criminal Code and Its Implications for Freedom of Expression on Social Media - Ario Setra Setiadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
The rapid expansion of social media has transformed Indonesia’s public communication environment, enabling broader civic participation while simultaneously generating new legal challenges related to online defamation and digital expression. Within this evolving digital public sphere, the application of criminal defamation provisions, particularly Article 27 paragraph (3) of the Electronic Information and Transactions Law (ITE Law) and defamation provisions within the Criminal Code, has generated significant controversy due to concerns regarding overcriminalization, legal ambiguity, and chilling effects on democratic discourse. This study reassesses the coherence and proportionality of Indonesia’s legal framework governing online defamation and freedom of expression in social media environments, with specific attention to Article 433 of the new Indonesian Criminal Code and the transitional regime under Law No. 1 of 2024 on the second amendment to the ITE Law. Employing a normative juridical approach supported by legislative, conceptual, case, and comparative legal analyses, the research draws on constitutional provisions, statutory regulations, judicial decisions, and international human rights instruments. The findings reveal structural problems in the current framework, including vague statutory definitions, overlapping norms between the ITE Law and the new Criminal Code, inconsistent law enforcement practices, and limited digital forensic capacity, which collectively foster overcriminalization and a chilling effect on legitimate digital expression. To address these challenges, the study proposes the Digital Expression Regulation Framework (DERF), a multidimensional model integrating digital rights, user behavior, legal boundaries, and enforcement mechanisms to balance reputational protection with democratic freedom of expression in Indonesia’s evolving digital public sphere.